2014
DOI: 10.1016/j.cmet.2013.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Pdx1 Maintains β Cell Identity and Function by Repressing an α Cell Program

Abstract: SUMMARY Pdx1 is a homeobox-containing transcription factor that plays a key role in pancreatic development and adult β-cell function. In this study, we traced the fate of adult β-cells after Pdx1 deletion. As expected, β-cell-specific removal of Pdx1 resulted in severe hyperglycemia within days. Surprisingly, a large fraction of Pdx1-deleted cells rapidly acquired ultrastructural and physiological features of α-cells, indicating that a robust cellular reprogramming had occurred. Reprogrammed cells exhibited a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
311
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 354 publications
(340 citation statements)
references
References 39 publications
13
311
1
Order By: Relevance
“…Dedifferentiation of beta cells is a topic of current islet research, and important contributions have been published by several groups in recent years during the course of this study [8,13,14]. In addition, Hang et al showed that MafA is required in adult beta cells for the maintenance of their phenotype but not for their initial differentiation [31], which is consistent with our results.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Dedifferentiation of beta cells is a topic of current islet research, and important contributions have been published by several groups in recent years during the course of this study [8,13,14]. In addition, Hang et al showed that MafA is required in adult beta cells for the maintenance of their phenotype but not for their initial differentiation [31], which is consistent with our results.…”
Section: Discussionsupporting
confidence: 81%
“…This result is supported by the increased expression of factors such as MafB that are transiently expressed in endocrine progenitors of the embryonic pancreas. MafB is also upregulated in the dedifferentiated beta cells of beta cellspecific Foxo1 KO mice with metabolic stress and Pdx1 KO mice [8,14], and induces genome-wide changes in DNA methylation [39]. Thus, MafB may be responsible for the upregulation of molecules including those beta cell disallowed genes in dedifferentiated beta cells by inducing epigenetic changes, which have been shown to regulate Slc16a1 expression [35,40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent reports demonstrate that forced expression of lineageinappropriate transcription factors causes islet cells to switch identity (Collombat et al, 2007;Collombat et al, 2009;Gao et al, 2014;Papizan et al, 2011;, which has been attributed to the similar chromatin states of alpha and beta cells (Bramswig et al, 2013). This establishes that beta cells can arise from nonbeta endocrine cells in the islet via direct transdifferentiation.…”
Section: Introductionmentioning
confidence: 92%
“…These factors favour low grade tissue inflammation and insulin resistance [10][11][12][13][14]. The ultimate cause of hyperglycaemia, however, is insufficient insulin secretion as a consequence of impaired glucoseinduced insulin secretion (GIIS), dedifferentiated beta cells or beta cell apoptosis [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%